Characterization of Lemongrass Extract (Cymbopagon citratus) Nanoemulsion and Its Application as an Antibiofilm Agent in Acrylic Resin - Vinna K. Sugiaman; Rosalina I. Saputri; Silvia Naliani; Jane A. V. Wibisono; Jeffrey; Wayan L. Demolsky; Wahyu Widowati; Agung Novianto (Journal of Pharmacy and Bioallied Sciences, 2024)
Background: An antimicrobial agent is needed for denture cleaning, such as lemongrass (LG), which has a bioactive antimicrobial component. Methods: This research analyzed LG extract nanoparticles with a particle size analyzer, ZPA, and biofilm formation inhibition on resin acrylic surfaces. Results: We found that there is high stability in nanoparticle size, while other concentrations, including chlorhexidine as a positive control, did not show any statistical differences. Conclusion: Lemongrass oil nanoemulsion has proved to be an antibiofilm and effective as a denture cleaning agent because of its ability to inhibit Streptococcus mutans and Candida albicans growth.